Pemetaan Hasil Ujian Nasional Matematika - Sumaryanta Sumaryanta; Nanang Priatna; Sugiman Sugiman (Pusat Pengembangan dan Pemberdayaan Pendidik dan Tenaga Kependidikan Matematika, 2019)
This study aims to map the results of the mathematics national examination. The research was conducted from October to November 2018. Data collection technique applied in this research was documentation technique. The data of this study were taken from PAMER released by Puspendik in 2016, 2017, and 2018. Data analysis was carried out in a quantitative descriptive model, and then the results were presented in the form of graphs and tables. The results of this study indicates that: 1) the scores of mathematics national examination of students in the last three years (2015/2016, 2016/2017, and 2017/2018) are considered low on all materials tested, and 2) nationally, the average scores of mathematics national examination almost in all provinces are condidered low at all levels of education.